The conceptual design and development of novel low cost sensors for measuring the relative light emission in the pre-millisecond stages of detonating explosive charges - Olivier, Marius (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2012.